2014
DOI: 10.1177/1741134315596012
|View full text |Cite
|
Sign up to set email alerts
|

Generic medicine: Boston University students’ perceptions and surprising lack of knowledge

Abstract: This project aims to compare knowledge, perceptions, and attitudes regarding generic medicines in an effort to illuminate the reasons for widely discrepant rates of generic utilization in different countries. While the United States has high rates of generic uptake (around 86%), and generic medicine utilization has saved the US healthcare system over $1 trillion in the past decade (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), similar figures are not seen in many other countries desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Utilizing generic medicines in place of their brands has been suggested as one area of health to reduce annual healthcare expenditure without compromising its delivered quality (1)(2)(3). Generic medicines are identical, or bioequivalent, to brand medicines in dosage form, safety, efficacy, route of administration, quality and intended medical use (4).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing generic medicines in place of their brands has been suggested as one area of health to reduce annual healthcare expenditure without compromising its delivered quality (1)(2)(3). Generic medicines are identical, or bioequivalent, to brand medicines in dosage form, safety, efficacy, route of administration, quality and intended medical use (4).…”
Section: Introductionmentioning
confidence: 99%
“…Governments and third-party payers promoted the use of GMs to limit the increasing health care costs without compromising health care quality [ 5 ]. In 2011, the use of US-FDA-approved generic medicines saved 158 billion dollars, and in the United States, the use of GM saved over 1 trillion dollars between 2003 and 2014 [ 1 , 10 ]. Therefore, a significant health care savings can be achieved if countries employ generic policies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical students’ trust would be improved by increasing their knowledge about generic drugs, and the strict approval and registration processes they go through before becoming available in the market. A study conducted by Tobin and Laing, on medical students from Boston University, showed that students would only choose generic drugs for certain illnesses ( Tobin and Laing, 2015 ). The current study, also, revealed that effectiveness, safety, and cost are the most important determinants of drug choice when participants were responding as future prescribers—followed by disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The current study, also, revealed that effectiveness, safety, and cost are the most important determinants of drug choice when participants were responding as future prescribers—followed by disease severity. In some studies participants have reported that visits from medical representatives, free drug samples, and promotions from pharmaceutical companies, would affect their choice of drugs ( Tobin and Laing, 2015 ; James et al, 2018 ; Bookwalter, 2021 ). In the current study, however, only 44 participants (11.3%) said that such factors would influence their decisions.…”
Section: Discussionmentioning
confidence: 99%